PENGARUH PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TIKET KONSUMEN DI KANTOR PENJUALAN GARUDA INDONESIA CABANG PUPUTAN DENPASAR - Ni Made Sonya Marina Dewi; Ida Ketut Kusumawijaya (Universitas Triatma Mulya, 2022)
This study aims to determine the effect of product, price and promotion on consumer ticket purchasing decisions at the Garuda Indonesia sales office, Puputan Denpasar Branch. Respondents in this study were all passengers who came to transact at the Garuda Indonesia sales office, Puputan Denpasar Branch. Total respondents in this research amounted to 94 people. In this study using statistical analysis through a computer program SPSS (Statistical For Social Science). The results of the instrument test in this study showed valid and reliable data. The results of this study indicate that product, price and promotion have a positive and significant effect on consumer ticket purchasing decisions at the Garuda Indonesia sales office, Puputan Denpasar branch